ANALYSIS OF THE INFLUENCE OF DIGITAL MARKETING ON THE CONSUMER BEHAVIOR OF STUDENTS OF THE STATE POLYTECHNIC OF CREATIVE MEDIA - Ridwan, Muhamad (Jurnal Ilmiah Publipreneur, 2025)
This study aims to analyze the influence of digital marketing on the consumptive behavior of students at Politeknik Negeri Media Kreatif. The research is based on the increasing use of digital and social media platforms as promotional tools that shape young consumers’ purchasing patterns. A quantitative approach with a descriptive associative method was employed. Data were collected through an online questionnaire distributed to 100 active students using a 6-point Likert scale. The results revealed that all items were valid and reliable, with Cronbach’s Alpha values of 0.838 for digital marketing and 0.920 for consumptive behavior. The regression equation obtained was Y = -21.34 + 1.05X, with a coefficient of determination (R²) of 0.3847. This indicates that digital marketing has a positive and significant influence on students’ consumptive behavior. These findings align with previous studies by Lestari and Hidayat (2023) and Kusuma and Sari (2022), which confirmed that digital promotions play a key role in increasing the consumptive tendencies of young consumers.